High-performance colorful semitransparent perovskite solar cells with phase-compensated microcavities - Lee, Kyu Tae; Jang, Ji Yun; Ha, Na Young; Lee, Soonil; Park, Hui Joon (Nano Research, 2018)
We demonstrate highly efficient multi-colored semitransparent perovskite solar cells that can create high angular tolerant controllable transmissive colors up to 60°, based on phase-compensated microcavities. The efficiency of the semitransparent colors was improved by impedance matching, which was enabled by placing a dielectric functional layer on top of traditional optical microcavities, with negligible influence on color pureness. The vast majority of the visible part of solar radiation is efficiently utilized for solar energy harvesting, achieving 10.47%, 10.66%, and 11.18% of efficiency for red, green, and blue (RGB) colored solar cells, respectively, while a very small proportion of the visible solar spectrum is used for structural coloration that can be readily tuned by altering the cavity medium thickness. The approach described herein can be suitable for a variety of applications such as display systems with ultra-low power consumption, highly efficient colorful solar panels, low-power wearable electronics, and energy-efficient optoelectronics. [Figure not available: see fulltext.].
Keywords: Color filters; Energy efficient; Functional layer; Optical cavities; Optical microcavities; Semi transparencies; Solar spectrum; Ultra-low power consumption; color filters; optical cavities; perovskite solar cells; semitransparency